Effect of a Mediterranean type diet on inflammatory and cartilage degradation biomarkers in patients with osteoarthritis - Jade Dyer; Glen Davison; Samuele Marcora; Alexis R. Mauger (2016)
To investigate the effects of a Mediterranean type diet on patients with osteoarthritis (OA).